Dante’s Commedia and the “Case” of the didascalus - Cicali, Gianni (Quaderni d'Italianistica)

(untitled) (Iter Press, 2024)
The relations between Dante’s Commedia and theatre are still a rich and, in some aspects, uncharted territory for research. In this essay, I will briefly outline the principal traits of medieval theatre and spectacle and present aspects of the dramaturgic and iconographic background of Dante’s major poem. Specific attention will be given to the analysis of Virgil, St. Bernard, Dante, and other characters of the Commedia as didascali. The role of the didascalus (maestro), sometimes called festaiuolo, in medieval religious theatre served multiple functions related to the theatre shows. I argue that Dante sometimes relies on narrative/dramatic patterns that can be associated with the role of the didascalus in medieval theatre and spectacle.